Crisis y resistencia en la novela Ceniza en la boca (2022) de Brenda Navarro (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
Hispanic American literature has tended, at least in general terms, to take a critical approach to various crises. Especially frequent are issues related to historical crises, such as dictatorships, social, economic or political conflicts, but it has also dealt with crises on an individual level, such as existential, emotional or identity crises. The following pages have two fundamental objectives, the first of which is to analyse how the main characters in Brenda Navarro's Ceniza en la boca (2022) face a profound identity crisis when they migrate to Spain. The novel's young Mexican siblings are victims of racism on their arrival in the country, with the consequent impact of this on the construction of their individual identities. The second objective is to highlight how this novel manages to give a twist to the literary approach to the identity crisis, insofar as, in addition to being the central theme of the story, it is also a form of resistance to the racism that has provoked it. Brenda Navarro invites us in Ceniza en la boca (2022) to rethink identity from more empathetic scenarios in the face of identities different from our own, and she achieves this with complex, multidimensional characters that foster a nuanced understanding of otherness. Finally, the methodological approach is based on the guiding knots of postcolonial studies.
Keywords: Brenda Navarro; Identity crisis; Racism; Resistance; Otherness